The Spatial Linkages of Manufacturing in Montreal and its Surroundings - Brooks, Stanley; Gilmours, James; Murrican, Kenneth (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1973)
It has generally been believed that the postulated agglomerative force of industrial concentrations expresses itself in economies in the transactions (linkages) between firms in the same concentration. This paper examines aspects of this long-held idea by considering material linkages of manufacturing in Montréal with a view to ascertaining the agglomerative strength of Montréal in regard to these linkages. More importantly, establishments are considered according to size and to location within the industrial complex in order to establish whether or not there is a relationship between these factors and the strength of linkage with the local economy.The overall linkage with Montréal is weak, but there is no doubt that the strength of linkage with Montréal varies inversely with the size of establishments. It was anticipated that the strength of linkage with Montréal would diminish from the centre to the edge of the industrial complex. In general, this does not prove to be true. In the case of purchase linkages the opposite occurs. Tentative explanation is given but further investigation is needed.